Prevalence and Correlates of Poor Sleep Quality Among Psychiatry Physicians in Saudi Arabia: A Cross‐Sectional Study - Najim Z. Alshahrani; Abdullah M. Alarifi; Wejdan Saqer Alotaibi; Afnan Abdulrahman Alsayed; Khalid Sultan Latif Alwasm; Alaa Abdulkarim Alhunti; Lana Alaa AlDahleh; Meaad Mohammed A Alshahrani; Abdalrhman M. Albeshry; Mohammed A. Aljunaid (Health Science Reports)
ABSTRACT Background and Aims Sleep issues pose a significant burden to public health and well‐being in Saudi Arabia. However, research evidence on sleep health among psychiatry physicians in this territory is limited. Therefore, to bridge the research gap, this study was designed to assess the prevalence and predictors of poor sleep quality among psychiatry physicians in the country. Methods This cross‐sectional study included 554 psychiatry physicians in Saudi Arabia from March to August 2023. Data were collected via online through a structured questionnaire (Google survey form). Sleep quality, the outcome variable of our study, was evaluated with the Pittsburgh Sleep Quality Index (PSQI; 19 items). Independent variables included sociodemographic and behavioral characteristics, sleep habits, major depression (assessed with Patient Health Questionnaire‐9), and anxiety (measured with Generalized Anxiety Disorder‐7) symptoms. Binary logistic regression analysis was performed to identify the correlates of poor sleep quality. Results Based on the PSQI, 61.3% of the study participants had poor‐quality sleep (age range: 24–56 years, male: 48.0%). The adjusted model revealed that male participants (AOR = 2.80, 95% CI = 1.70–4.61) and those who had on‐call duties ≥ 2 times per week (for three/four per week: AOR = 3.41, 95% CI = 1.89–6.14) were at higher risk of developing poor sleep quality compared to their respective counterparts. Participants with depressive symptoms (AOR = 3.46, 95% CI = 1.60–7.48) and smoking habits (AOR = 3.47, 95% CI = 1.32–9.08) had higher odds of developing poor sleep quality than their counterparts. Moreover, participants who always used their smartphone/laptop before going to bed were more likely to have poor sleep quality than those who never used such (AOR = 3.15, 95% CI = 1.31–7.60). Conclusion Poor sleep quality is extremely prominent among psychiatry physicians in Saudi Arabia. Male sex, higher on‐call duty, smoking habits, depression, and smartphone/laptop use before bedtime were significantly associated with poor sleep quality. These findings emphasize the need for sleep‐health promotion interventions for Saudi psychiatry physicians.